PERSPECTIVE OF ENGLISH TEACHERS ON NATIONAL ASSESSMENT (MINIMUM COMPETENCY ASSESSMENT, SURVEY OF CHARACTER AND LEARNING ENVIRONMENT) - Zuri, Tella Amy Novera Afan (Langue (Journal of Language and Education), 2023)
This research is aimed to discuss about perspective of English teachers on National assessment in term of minimum competency assessment, survey of character and survey of learning environment as three main components of National assessment. This qualitative research was using interview with five English teachers in Jambi Province as research participants. Pseudonym were used in this research to protect the privacy of research participants. Five participants will be identified as T1, T2, T3, T4 and T5. The results of this study indicated that only T1 had complete knowledge and comprehension about National assessment. Three of five English teachers (T2, T3 and T4) had knowledge and comprehension about the National assessment in general, but did not have specific knowledge and comprehension of the National assessment, while one of English teachers (T5) had no idea and did not understand at all related to knowledge and comprehension of the National assessment as a comprehensive evaluation program. All participants (T1, T2, T3, T4 and T5) have never attended seminar, training and any form of socialization about National assessment. It can be concluded that there is a lack of optimal socialization regarding the National assessment conducted by the government for English teachers and all parties in this evaluation program such as headmaster, teachers and student. It is causing all research participants (T1, T2, T3, T4 and T5) still do not have sufficient knowledge and comprehension of the National assessment and its implementation.